Effect of EGCG–Methacrylate-Functionalized Resin Infiltrant on White Spot Lesions: An In Vitro Study - Karin Landmayer; Bruna de Oliveira Iatarola; Talita Portela Pereira; Raquel Shimizu Mori; Alyssa Teixeira Obeid; Mariele Vertuan; Daniela Alvim Chrisostomo; Ana Carolina Magalhães; Lulwah Alreshaid; Paulo Henrique dos Santos; Anuradha Prakki; Luciana Fávaro Francisconi-dos-Rios (Journal of Functional Biomaterials)
This study evaluated the color change (ΔE00) and penetration depth (PD) of white spot lesions (WSLs) infiltrated with the resin infiltrant (Icon®) functionalized with methacrylate epigallocatechin-3-gallate (EGCG). To introduce polymerizable double bonds, EGCG was reacted with methacryloyl chloride (EM). Subsequently, the Icon resin infiltrant (I) was loaded with neat EGCG (IE) or EGCG–methacrylate (IEM) at 2 wt% each. WSLs were created on bovine enamel blocks and treated with I, IE, or IEM. Sound and untreated enamel surfaces were used as controls (C). Infiltrant PD (%) was determined by Confocal Laser Scanning Microscopy (CLSM, n = 12) analysis. For color change (ΔE00) determination (n = 14), ΔL, Δa, and Δb, half of each sample was kept sound as a reference area. The color was determined with a spectrophotometer. Data were statistically evaluated (p = 0.05). Surface morphology was obtained as a qualitative response variable using 3D CLSM. PD (%) did not differ statistically for I, IE, and IEM (p = 0.780). Groups I and IEM showed similar performance on color change (ΔE00) compared to the control group, while IE exhibited intermediate results, with no significant difference observed between the untreated, I, and IEM groups (p < 0.001). IEM promoted the masking of the WSL color without interfering with the PD.